Differentials of the 2nd kind on a product surface - J. C. Wilson (International Journal of Mathematics and Mathematical Sciences)
This paper deals with the problems of representing an arbitrary double differential of the second kind, defined on a surface which is the topological product of two curves, in terms of the products of simple differentials of the second kind on the two curves. The curves are assumed to be non-singular and irreducible in a complex projective 2-space.